A qualitative exploration of oral health care among stroke survivors living in the community. (19th June 2020) - O'Malley, Lucy; Powell, Rachael; Hulme, Sharon; Lievesley, Matthew; Westoby, Wendy; Zadik, Jess; Bowen, Audrey; Brocklehurst, Paul; Smith, Craig J.
Abstract: Background: Dental disease is highly prevalent in people with stroke. Stroke survivors regard oral hygiene as an important, yet neglected, area. The aim was to explore experiences of and barriers to oral care, particularly in relation to oral hygiene practice and dental attendance, among stroke survivors in the community. Methods: This was a qualitative study incorporating a critical realist approach. Interviews were conducted with community‐dwelling stroke survivors requiring assistance with activities of daily living, and focus groups were held with health and care professionals. Interviews and focus groups were recorded and transcribed verbatim. Thematic analysis was conducted. Results: Twenty‐three stroke survivors were interviewed, and 19 professionals took part in 3 focus groups. Professionals included nurses, speech and language therapists, occupational therapists, dieticians, professional carers and dental staff. Interviews revealed difficulties in carrying out oral hygiene self‐care due to fatigue, forgetfulness and limb function and dexterity problems. Routine was considered important for oral hygiene self‐care and was disrupted by hospitalization resulting from stroke. Professionals highlighted gaps in staff training and confidence in supporting patients with oral care. Access to dental services appeared particularly problematic for those who were not registered with a dentist pre‐stroke. Conclusion: Oral hygiene routines may be disrupted by stroke, and resulting disabilities may make regular oral self‐care more difficult. This study has identified specific barriers to oral hygiene self‐care and dental service access. Findings from this study are feeding into the development of an intervention to support stroke survivors with oral care.